Оцінювання митних ургентних інструментів антикризового управління підприємствами в умовах європейської інтеграції - Юринець, О. В.; Адамів, М. Є.; Yurynets, O. V.; Adamiv, M. Ye. (Видавництво Львівської політехніки, 2022)
Обґрунтовано актуальність оцінювання митних ургентних інструментів антикризового управління підприємствами в умовах європейської інтеграції. Критично проаналізовано існуючі підходи до діагностики митних інструментів на різних рівнях. Уточнено сутність показників оцінювання митних ургентних інструментів антикризового управління підприємствами. Розвинуто перелік принципів добору показників оцінювання митних ургентних інструментів антикризового управління підприємствами. Удосконалено полірівневу систему показників оцінювання митних ургентних інструментів антикризового управління підприємствами.

The intensification of military and political instability and the activization of European integration processes necessitate the development and use of precisely urgent instruments at different levels and in different spheres. In the conditions of fulfillment of European integration obligations one of the priority directions requiring urgent reforms is the customs system of Ukraine. Along with the already implemented reforms in the customs sphere, there are still a number of unresolved tasks that require the introduction of effective and progressive tools. At the same time, the effectiveness of such tools is determined on the basis of a comprehensive information base, which is the result of a targeted assessment. Thus, an important problem today is the selection of a reasonable list of indicators to diagnose the optimality of customs urgent instruments to ensure the successful European integration of Ukraine. Indicators of evaluation of customs urgent instruments should be understood as measures of effectiveness of formation and use of customs urgent instruments at different levels in the context of urgent solution of urgent problems of customs nature, elimination or minimization of their negative impact, primarily on export-import operations of enterprises, increasing the favorability of customs services of foreign economic activity subjects and activation of international trade. In order to assess the effectiveness of customs urgent instruments for effective solution of urgent problems of the state customs system functioning and provision of its progressive development the system of diagnostic indicators was prepared based on a number of principles: purposefulness, urgency, anti-crisis, activation, relationship with stakeholders, multilevel orientation, the relationship with European integration, harmonization, specificity, adaptability, optimality, accessibility, effectiveness, information diversity. The developed typology of diagnostic indicators hierarchically differentiates such indicators to assess the impact of customs urgent instruments at different levels (mega-, macro-, meso- and micro-levels) of national economy in order to provide favorable customs services to enterprises as a precondition for enhancing export-import activities in the conditions of Euro-integration transformations.
Evaluation of customs urgent instruments of anti – crisis management of enterprises in the conditions of European integration
Keywords: митні інструменти; ургентні інструменти; оцінювання; антикризове управління; показники; рівні; митна система; європейська інтеграція; customs instruments; urgent instruments; evaluation; anti-crisis management; indicators; levels; customs system; European integration; 339.5